2017
DOI: 10.1086/689869
|View full text |Cite|
|
Sign up to set email alerts
|

Unbalanced Random Matching Markets: The Stark Effect of Competition

Abstract: We study competition in matching markets with random heterogeneous preferences and an unequal number of agents on either side. First, we show that even the slightest imbalance yields an essentially unique stable matching. Second, we give a tight description of stable outcomes, showing that matching markets are extremely competitive. Each agent on the short side of the market is matched with one of his top choices, and each agent on the long side either is unmatched or does almost no better than being matched w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
176
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(184 citation statements)
references
References 32 publications
7
176
1
Order By: Relevance
“…an arbitrarily large share of all the men in the market under the stable matching most preferred by the women (W-optimal matching), whereas under the stable matching that is most preferred by all men (M-optimal matching), their match is ranked above a share that is arbitrarily close to zero. In more recent work, Ashlagi, Kanoria, and Leshno (2013) showed that this finding depends crucially on both sides of the market having a (close to equal) number of participants. Our results concern only the observable implications of pairwise stability, where we find that, for large markets, the differences in distributions of matched characteristics resulting for different stable matchings become irrelevant with no regard to the relative number of agents on either side of the market.…”
Section: Related Literaturementioning
confidence: 96%
“…an arbitrarily large share of all the men in the market under the stable matching most preferred by the women (W-optimal matching), whereas under the stable matching that is most preferred by all men (M-optimal matching), their match is ranked above a share that is arbitrarily close to zero. In more recent work, Ashlagi, Kanoria, and Leshno (2013) showed that this finding depends crucially on both sides of the market having a (close to equal) number of participants. Our results concern only the observable implications of pairwise stability, where we find that, for large markets, the differences in distributions of matched characteristics resulting for different stable matchings become irrelevant with no regard to the relative number of agents on either side of the market.…”
Section: Related Literaturementioning
confidence: 96%
“…54 53 See Dubins and Freedman (1981) and Roth (1982a) on incentives in the one-to-one marriage problem, and Roth (1985) when there is many-to-one matching as in the medical match. Roth and Peranson (1999) observed the small size of the set of stable matchings, and Ashlagi, Kanoria, and Leshno (2017) have given a compelling theoretical account of why we should expect the set of stable matchings to be small in these kinds of matching models. In simple models (e.g., of one-to-one matching) this in turn implies that profitably manipulating preferences will not be a viable option for virtually all participants, because manipulation of preferences cannot move outcomes outside of the set of stable matchings (see Demange, Gale, and Sotomayor 1987;Roth 2015c).…”
mentioning
confidence: 99%
“…All results in Section 3 extend to the case of societies unbalanced in their gender ratio. Regarding the expected gains from integration, Ashlagi et al (2017) show that the spouse rank for men and women in the MOSM roughly reverses if there are more men than women. Therefore, if we merge several societies, all in which there are more men than women, the expected gains from integration roughly reverse as well.…”
Section: Resultsmentioning
confidence: 98%
“…This result extends to manyto-one SMPs (Theorem 5 in Kelso and Crawford, 1982, Theorems 1 and 2 in Crawford, 1991, and Theorems 2.25 and 2.26 in Roth and Sotomayor, 1992). Ashlagi et al (2017) describe the exact magnitude of these welfare changes in random MPs. Toda (2006) uses this monotonicity property to characterize the set of stable outcomes.…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation